2011
DOI: 10.1108/17410391111166521
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting knowledge transfer success in information systems outsourcing

Abstract: Despite increased research interest on knowledge transfer in information systems (IS) outsourcing, the field still lacks sound and holistic understanding of the key factors influencing knowledge transfer success. The present paper attempts to provide a synthesis of existing theoretical perspectives and empirical findings related to the factors that facilitate or hamper knowledge transfer success in IS outsourcing. The data collection method is discussed and the key findings are presented. Conclusion is drawn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 76 publications
4
59
0
Order By: Relevance
“…It is a clear indication that Gathering information and experience among teams 0.108 [7] 0.0388 [7] 0.895 [12] 0.0302 [7] C 12 Sharing knowledge and experience among team members 0.104 [11] 0.0327 [11] 0.917 [7] 0.0300 [11] C 13 Understanding goals, tasks and responsibilities over the project outcome 0.098 [16] 0.0308 [16] 0.643 [6] 0.0198 [38] C 14 Team participation and communication relationship 0.100 [14] 0.0313 [14] 0.750 [25] 0.0235 [3] C 15 Participation in helping each other 0.101 [12] 0.0317 [12] 0.685 [23] 0.0217 [25] C 16 Specialty and knowledge creation ability among teams 0.101 [12] 0.0317 [12] 0.815 [17] 0.0259 [13] C 17 Learning and sharing the technical information and work materials of teams 0.097 [2] 0.0305 [2] 0.805 [19] 0.0246 [2] C 18 Team members' ability to provide assistance in solving problems 0.099 [15] 0.0312 [15] 0.805 [19] 0.0251 [14] C 19 Clear vision to solve their professional problems towards the project outcome 0.097 [2] 0.0304 [17] 0.685 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a clear indication that Gathering information and experience among teams 0.108 [7] 0.0388 [7] 0.895 [12] 0.0302 [7] C 12 Sharing knowledge and experience among team members 0.104 [11] 0.0327 [11] 0.917 [7] 0.0300 [11] C 13 Understanding goals, tasks and responsibilities over the project outcome 0.098 [16] 0.0308 [16] 0.643 [6] 0.0198 [38] C 14 Team participation and communication relationship 0.100 [14] 0.0313 [14] 0.750 [25] 0.0235 [3] C 15 Participation in helping each other 0.101 [12] 0.0317 [12] 0.685 [23] 0.0217 [25] C 16 Specialty and knowledge creation ability among teams 0.101 [12] 0.0317 [12] 0.815 [17] 0.0259 [13] C 17 Learning and sharing the technical information and work materials of teams 0.097 [2] 0.0305 [2] 0.805 [19] 0.0246 [2] C 18 Team members' ability to provide assistance in solving problems 0.099 [15] 0.0312 [15] 0.805 [19] 0.0251 [14] C 19 Clear vision to solve their professional problems towards the project outcome 0.097 [2] 0.0304 [17] 0.685 …”
Section: Resultsmentioning
confidence: 99%
“…The final section includes the conclusion of the study and addresses the significance of knowledge transfer effectiveness on GSD teams. Earlier studies have addressed the characteristics of knowledge and significance of knowledge transfer in IS outsourcing success [2,[11][12][13][14][15][16]. Moreover, most of the studies have substantially acknowledged the significance of socialization, externalization, combination, and internalization (SECI) in knowledge management theory [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has argued that the factors that influence knowledge application include absorptive capacity (Al-Salti et al, 2010), trust (Gupta and Govindarajan, 2000), culture (Karlsen and Gottschalk, 2004), reward (Evaristo, 2005), willingness to apply knowledge (Liyanage et al, 2009) and expertise (Salsali et al, 2009). Among these factors, the study found trust, culture and absorptive capacity as the critical factors in knowledge application in Ghanaian industries, confirming the findings of Gupta Note: The means are determined by using a five-point Likert scale rating from strongly agree (5) to strongly disagree (1).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…According to Al-Salti and Hackney (2011), there are a number of problems, such as the ambiguity of knowledge, the tacit knowledge, the di±cult relationship between source and the receiver, the complexity and the context of knowledge, the lack of motivation and reliability of the transmitter, the lack of motivation and retentive capacity from receiver. Albino et al (1998) describe the steps that should be taken and the restrictions that should be imposed to prevent a company losing its competitiveness during a TT due to access by third parties to certain knowledge without appropriate controls.…”
Section: Introductionmentioning
confidence: 99%